Validation of a nonlinear wave decomposition method including shoaling for irregular waves - de Ridder, Menno; den Bieman, Joost; Kramer, Jan (Journal of Coastal and Hydraulic Structures, 2024)
It is important to decompose the signals when performing physical model experiments. In this paper, a nonlinear decomposition method is extended with the effects of a sloping bed. The approach is validated based on synthetic signals and numerical simulations. Verification with linear synthetic signals shows that the effect on the wave height is limited for intermediate water depth, but increases for shallow water depth with an error of up to 4%. Moreover, when not accounted for a sloping bed the wave height at the first wave gauge is overestimated in shallow water and underestimated in deep water. The results from the numerical simulations show that a shoaling coefficient for the bound waves based on the water depth ratio with a power 1 is reasonably accurate for the sub-harmonics but not valid for the higher harmonics. In addition, it is recommended to verify this assumption for a large range of test conditions. When applying both the method without and with the effects of a sloping bed on physical model experiments, the average differences are 1 % with a maximum up to 4 % in terms of the wave height.